Time to change the approach to stuttering - Pakura, Monika; Szymczakowska, Joanna; Węsierska, Katarzyna (Papers in Linguistics, 2024)
The article describes stuttering and related issues. The authors outline how the results of scientific research have changed the approach to stuttering in the world and Polish speech therapy. They stress the importance of updating therapists’ knowledge and its dissemination among the public. They discuss selected myths related to the perception of stuttering, interpreting them in the context of scientific evidence. They also point out the validity of viewing stuttering as a form of verbal diversity. The article lists several activities that can help support people who stutter and improve their quality of life. New insights into the role of the speech therapist in stuttering speech therapy intervention are also presented in the study.